HEAT EXCHANGER WITH INCREASED HEAT TRANSFER EFFICIENCY AND A LOW-COST METHOD OF FORMING THE HEAT EXCHANGER - CALANNI DANIEL J; GIACOMA LAWRENCE M (2006)
The efficiency of a heat exchanger is significantly improved by connecting walls to an air flow structure, which has first grooves formed in the top surface of the structure and second grooves formed in the bottom surface of the structure, that block off alternating ends of the first and second grooves such that a first air source can only flow through the first grooves and a second air source can only flow through the second grooves.